The Effects of Pro-Inflammatory Cytokines on Human Body and Their Relation with Diseases (Review Article) - Khalid Shaalan Sahab; Mohammed Asaad Mahdi; Ammar M. K. AL-Azzawi (ASJ - Academic Science Journal, 2023)
Cytokines are important mediators in inflammatory disorders that affect the entire body.Signaling molecules called pro-inflammatory cytokines, also known as inflammatorycytokines, are released by the immune system cells including macrophages and T helper cells(Th), which promote inflammation. Interleukin-1 (IL-1), Interleukin-6 (IL-6), and Interleukin-12 (IL-12) are pro-inflammatory cytokines which are released during the inflammations. Otherinflammatory cytokines are interleukin-18 (IL-18), interferon-gamma (IFN-γ), tumour necrosisfactor-alpha (TNF-α), and granulocyte-macrophage colony-stimulating factor (GM-CSF)mediate the innate immune response. Immune cells, and activated macrophages releaseinflammatory cytokines to orchestrate inflammatory responses; however, continuous chronicinflammation release high levels of inflammatory cytokines creating inflammatorymicroenvironment that are associated with a variety of illnesses, including atherosclerosis,cancer, and other conditions. Although the quantity of inflammation caused by the productionof pro-inflammatory cytokines is influenced by ageing, health preservation needs a balancebetween pro- and anti-inflammatory cytokines. Inflammatory diseases therapy employsmonoclonal antibodies that can neutralize inflammatory cytokines or block their receptors.Conclusion: A review of previous research shows a strong correlation between cytokines andinflammatory diseases.